Medical School Curricular Changes and Their Impact on Mental Health during the Onset of the COVID-19 Pandemic - Al Kassab, Leen; Fozouni, Laila; Reynolds, Christopher; Pham, Phuong; Dobiesz, Valerie (Avicenna Journal of Medicine, 2024)
Objectives The main objectives were to identify and categorize the curricular changes that occurred in U.S. medical schools during the onset of the coronavirus disease 2019 (COVID-19) pandemic, and to identify the relationship between curricular changes and COVID-19 surges and student mental health.Methods This Institutional Review Board-approved study consisted of a voluntary online survey of U.S. medical students. A convenience sample of students was reached through Facebook groups, medical student organizations, and administrators. The survey consisted of questions about demographics, curricular changes, and mental health. Univariate and backward stepwise multivariate linear regression were used to assess associations between mental health outcomes and demographic characteristics, curricular changes, and stressors.Results Four-hundred and nine medical students completed the survey from 21 states between May 29, 2020, and August 29, 2020. Seventy-nine percent of respondents reported continuing their basic science curricula virtually. Forty-five percent reported that rotations continued virtually; those reported being offered virtually included internal medicine (77%), family medicine (78%), surgery (70%), obstetrics/gynecology (73%), pediatrics (74%), and psychiatry (76%). The majority of students reported that core clerkships (78%) and subinternships (86%) were not allowed, and away rotations were universally canceled. In univariate linear regression, having in-person subinternships and core clerkships allowed, as well as not relocating for coursework or residence (experienced by 35% of students), was associated with improved mental health outcomes, while experiencing graduation changes (15%) or being from the Southern region was associated with worse outcomes (p < 0.001).Conclusion During the early COVID-19 pandemic, students reported that their medical schools adapted by converting to virtual platforms for basic science and core clerkships. Allowing in-person rotations and limiting relocation were associated with improved mental health outcomes among students. Limitations included sample size, selection bias, and student perceptions.
Keywords: medical education; curricular adaptations; mental health; COVID-19